Buka Luwur as A Media of Education and Social Solidarity of Kudus Community - Farihah, Irzum; Ismanto, Ismanto (AL-TAHRIR, 2019)
Abstract: Buka Luwur is an annual ritual that has become a tradition of Kudus community. It is a moment of respecting Kanjeng Sunan Kudus by providing some meal. This tradition is not only attended by Kudus inhabitants and Muslims around it but also people from various regions in Java. Buka Luwur ritual accepts various forms of sadaqah which will be distributed to all residents who are devoted. This article aims to find out the daâ€™wah of Javanese society through a series of Buka Luwur ritual in Kanjeng Sunan Kudus tomb, which was followed by various community groups, from santri to abangan communities, by using a sociological theory approach. The research method used was qualitative, while the respondents in this study were leaders, committees, communities around the research location, and residents who attended this ritual. Data collection techniques used were observation and in-depth interview. The data analysis used in the analysis process included reduction, data presentation, and conclusion. The results of this article: First, Buka Luwur is not only a series of agenda in commemorating Kanjeng Sunan Kudus haul but also as a part of Javanese Islamic preaching both verbally (bi al-qaul) and social actions (bi al-af'al). Second, Buka Luwur is used as a medium to build social solidarity among all groups. Ø§Ù„Ù…Ù„Ø®Øµ: Ø¨ÙˆÙƒØ§ Ù„ÙˆÙˆØ± Ø¹Ø§Ø¯Ø© ÙˆØ´Ø¹Ø§Ø¦Ø±Ø© ÙŠØØªÙÙ„ Ø¨Ù‡Ø§ Ø´Ø¹Ø¨ Ù…Ø¯ÙŠÙ†Ø© Ù‚Ø¯Ø³ Ø¬Ø§ÙˆÙ‰ Ø§Ù„ÙˆØ³Ø·Ù‰ Ø³Ù†ÙˆÙŠØ§ØŒ ÙˆÙŠØ¹Ù‚Ø¯ Ù‡Ø°Ø§ Ø§Ù„Ø§ØØªÙØ§Ù„ ØªØ¹Ø¸ÙŠÙ…Ø§ ÙˆØªÙƒØ±ÙŠÙ…Ø§ Ù„Ù„Ø³ÙŠØ¯ Ø³ÙˆÙ†Ø§Ù† Ù‚Ø¯Ø³ ÙˆÙ‡Ùˆ Ù…Ù† Ø£Ø¹Ø¶Ø§Ø¡ Ø£ÙˆÙ„ÙŠØ§Ø¡ Ø§Ù„ØªØ³Ø¹Ø© ÙŠØ¹Ù†ÙŠ Ø¨ÙˆÙƒØ§ Ù„ÙˆÙˆØ± Ù‡Ùˆ Ø¥Ø¨Ø¯Ø§Ù„ Ø§Ù„Ø³Ø§ØªØ± kain) Â Â Â Â (nisan Ø§Ù„Ù‚Ø¯ÙŠÙ… .ÙˆÙŠØØ¶Ø± Ù‡Ø°Ø§ Ø§Ù„Ø§ØØªÙØ§Ù„ Ù„Ø§ ÙŠÙ‚ØªØµØ± Ù…Ù† Ù…Ø³Ù„Ù…ÙŠÙ† Ù‚Ø¯Ø³ ÙˆØÙˆÙ„Ù‡Ø§ ÙØØ³Ø¨ Ø¨Ù„ ÙŠØØ¶Ø±Ù‡ Ø§Ù„Ù…Ø³Ù„Ù…ÙˆÙ† Ù…Ù† Ø§Ù„Ù…Ù†Ø§Ø·Ù‚ Ø§Ù„Ø¨Ø¹ÙŠØ¯Ø©. ÙˆØ¬Ù…Ø¹ Ù„Ø¬Ø§Ù† Ø§Ù„Ø§ØØªÙØ§Ù„ Ø§Ù„Ø¥Ù†ÙØ§Ù‚ ÙˆØ§Ù„ØµØ¯Ù‚Ø© ÙˆÙˆØ²Ø¹Ù‡Ø§ Ù„Ø¬Ù…ÙŠØ¹ Ø§Ù„ØØ§Ø¶Ø±ÙŠÙ†ØŒ ÙˆØºØ±Ø¶ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù„Ù…Ø¹Ø±ÙØ© Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¯Ø¹ÙˆØ© Ø¹Ù†Ø¯ Ø´Ø¹Ø¨ Ø¬Ø§ÙˆÙ‰ Ø¨Ø·Ø±ÙŠÙ‚ Ø³Ù„Ø³Ù„Ø© Ø§Ù„Ø§ØØªÙØ§Ù„ Ø§Ù„Ø°ÙŠ ÙŠØ´Ø§Ø±Ùƒ ÙÙŠÙ‡ Ø¬Ù…Ø¹ Ù…Ù† Ø³Ø§Ù†ØªØ±ÙŠ ÙˆØºÙŠØ±Ù‡ Ù…Ù† Ø£Ø¨Ø§Ù†Ø¬Ø§Ù† Ø¹Ù„Ù‰ Ù†Ù‡Ø¬ Ø§Ù„Ø§Ø¬ØªÙ…Ø§ Ø¹ÙŠØ© ÙˆØ£Ù…Ø§ Ù…Ù†Ù‡Ø¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙÙ‡Ùˆ Ø¨ØØ« Ù†ÙˆØ¹ÙŠ ÙˆÙƒÙŠÙÙŠØŒ ÙˆØ§Ù„Ù…Ø³ØªØ·Ù„Ø¹ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ø³Ø§Ø¯Ø©ØŒ ÙˆÙ„Ø¬Ø§Ù† Ø§Ù„Ø§ØØªÙØ§Ù„ØŒ ÙˆØ´Ø¹Ø¨ Ù‚Ø¯Ø³ØŒ ÙˆØ·Ø±ÙŠÙ‚ Ø¬Ù…Ø¹ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ù‡ÙŠ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ø§Ø³ØªÙ‚Ø±Ø§Ø¡ØŒ ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø§Ù„Ø§Ù†Ø®ÙØ§Ø¶ ÙˆØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª ÙˆØ§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬ .ÙˆØ£Ù…Ø§Ø®Ù„Ø§ØµØ© Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙÙ‡ÙŠ ÙƒØ§Ù„Ø¢ØªÙŠØ©: Ø§Ù„Ø£ÙˆÙ„Ù‰ØŒ Ø³Ù„Ø³Ù„Ø© Ø§ØØªÙØ§Ù„ Ø¨ÙˆÙƒØ§ Ù„ÙˆÙˆØ±ØŒ Ùˆ Ø°ÙƒØ±Ù‰ ÙˆÙØ§Ø© Ø§Ù„Ø³ÙŠØ¯ Ø³ÙˆÙ†Ø§Ù† Ù‚Ø¯Ø³ØŒ ÙˆØ°Ù„ÙƒØŒ Ø¨Ø¹Ø¶ Ù…Ù† Ø¯Ø¹ÙˆØ© Ù…Ø³Ù„Ù… Ø¬Ø§ÙˆÙ‰ Ù‚ÙˆÙ„Ø§ ÙˆÙØ¹Ù„Ø§. Ø§Ù„Ø«Ø§Ù†ÙŠØ©ØŒ Ø¨ÙˆÙƒØ§ Ù„ÙˆÙˆØ± ÙƒÙˆØ³ÙŠÙ„Ø© ÙÙŠ Ø¨Ù†Ø§Ø¡ ØªÙƒØ§ÙÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ù„Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø·Ø§Ø¦ÙÙŠØ©.Abstrak: Buka Luwur merupakan ritual tahunan yang sudah menjadi tradisi masyarakat Kudus dan dijadikan momen penghormatan terhadap Kanjeng Sunan Kudus dengan penggantian luwur makan. Tradisi tersebut tidak hanya dihadiri dari masyarakat Kudus dan yang beragama Islam saja, namun dari berbagai daerah di pulau Jawa. Ritual Buka Luwur juga menerima berbagai bentuk shadaqah yang akan dibagikan kepada seluruh warga yang mengahdiri. Artikel ini bertujuan untuk mengetahui dakwah masyarakat Jawa melalui rangkaian ritual Buka Luwur makam Kanjeng Sunan Kudus yang diikuti berbagai kelompok masyarakat, mulai kalangan santri sampai abangan dengan pendekatan teori sosiologis. Metode penelitian yang digunakan adalah kualitatif, sedangkan responden dalam penelitian ini adalah para tokoh, panitia, masyarakat sekitar lokasi penelitian, dan warga yang mengikuti ritual buka luwur. Teknik pengumpulan data yang digunakan adalah observasi dan indept interview, sedangkan pada analisis data akan digunakan proses analisis meliputi reduksi, penyajian data, dan penyimpulan. Hasil dari artikel ini: Pertama, rentetan acara buka luwur selain untuk memperingati haul Kanjeng Sunan Kudus, juga menjadi bagian dakwah Islam masyarakat Jawa baik secara lisan (bi al-qaul) maupun tindakan sosial (bi al-afâ€™al). Kedua, Buka Luwur dijadikan sebagai media untuk membangun solidaritas sosial masyarakat dari semua golongan.